2010
DOI: 10.1007/s10798-009-9111-y
|View full text |Cite
|
Sign up to set email alerts
|

The teacher–community of practice–student interaction in the New Zealand technology classroom

Abstract: In New Zealand in order to provide authentic learning experiences teachers are counselled to access Communities of Practice (CoP) (Ministry of Education 2007). This research provides information about teachers' interactions with CoPs and the implication of this access on their pedagogy. A range of interactions occurred which was influenced by how teachers perceived this use of a CoP representative in their classrooms. These styles of interactions were used by the teachers to create a 'deep, broad learning expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Informative approach to adopt SAP could lead farmers to make up their mind in order to be a part of decision-making process. The double-ended arrow in Figure 4 shows the linkage between the awareness and information which represent the knowledge transfer process also known as a dual process (Kahneman, 2003; Slatter and France, 2011). Furthermore, a knowledge transfer process indicates that information influences the awareness and judgment of the farmers v the adoption of SAP.…”
Section: Theories Based On Knowledge Transfermentioning
confidence: 99%
“…Informative approach to adopt SAP could lead farmers to make up their mind in order to be a part of decision-making process. The double-ended arrow in Figure 4 shows the linkage between the awareness and information which represent the knowledge transfer process also known as a dual process (Kahneman, 2003; Slatter and France, 2011). Furthermore, a knowledge transfer process indicates that information influences the awareness and judgment of the farmers v the adoption of SAP.…”
Section: Theories Based On Knowledge Transfermentioning
confidence: 99%
“…We were able to identify who held the 'locus of control' which is defined as the person who controlled the teacherCoP representative-student interaction (Slatter and France 2010). We observed that who held the 'locus of control' influenced these teachers' pedagogy.…”
Section: Resultsmentioning
confidence: 96%
“…When considering the dance metaphor in relation to this research we suggest that an initial paper examined why and how teachers became involved with a Community of Practice parallels receiving an invitation to a dance and deciding if it is worthwhile to go (Slatter and France 2008). The second paper we wrote examined how teachers made contact and managed this CoP representative interaction (Slatter and France 2010) and could be explained through the dance metaphor when you are at the dance and checking out who was there. The focus of this paper is to report on the complexity of how teachers plan and implement a CoP interaction in their classroom just as if you were dancing the night away.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative case study research approach (Stake 1995) has been common in studying CoPs for technology integration (Fuller et al, 2005;Hsu & Sharma, 2008;Slatter & France, 2011). The purpose of the approach is to build analytical generalisations, or theory, grounded in data.…”
Section: Methodsmentioning
confidence: 99%